A new species of Aconitum (Ranunculaceae) from Eastern Himalaya - Tiwary, Raghuvar; Singh, Harsh; Adhikari, Dibyendu; Singh, Prem Prakash; Barik, Saroj Kanta (Phytotaxa, 2019)
Aconitum tawangense, a new species from Tawang, Eastern Himalaya is described and illustrated here. This newly described species differ in the shape, size and vestiture of the sepals from its allied taxa A. assamicum and A. orochryseum. Other distinguishing characters include the colour of the petals and number of the carpels. The species was also assessed for its threat status.